2012
DOI: 10.1111/j.1526-4637.2011.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep Tissue Hypersensitivity to Pressure Pain in Individuals with Unilateral Acute Inversion Ankle Sprain

Abstract: This study showed the presence of localized pressure pain hypersensitivity over ankle ligaments in patients with unilateral acute inversion ankle sprain, confirming the presence of localized peripheral sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…32 It has also recently been demonstrated that localized mechanical pain hypersensitivity over ankle ligaments and the lateral malleolus exists in individuals with lateral ankle sprains. 26 This suggests that the peripheral sensitization secondary to the acuteness of the injury postlateral ankle sprain may be positively affected by myofascial techniques. 26 We also found significantly greater increases in PPTs over the affected leg in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…32 It has also recently been demonstrated that localized mechanical pain hypersensitivity over ankle ligaments and the lateral malleolus exists in individuals with lateral ankle sprains. 26 This suggests that the peripheral sensitization secondary to the acuteness of the injury postlateral ankle sprain may be positively affected by myofascial techniques. 26 We also found significantly greater increases in PPTs over the affected leg in the experimental group.…”
Section: Discussionmentioning
confidence: 99%
“…26 This suggests that the peripheral sensitization secondary to the acuteness of the injury postlateral ankle sprain may be positively affected by myofascial techniques. 26 We also found significantly greater increases in PPTs over the affected leg in the experimental group. Again, effect sizes were large, supporting a clinical effect of the intervention over mechanical sensitivity in those points previously found to be hypersensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is evidence of contralateral sensory perception changes in people with tendinopathy,55 this can equally reflect persistent nociceptive drive from the local tissue. Acute pain conditions, such as acute inversion ankle sprain, also caused secondary hyperalgesia;56 however, this can be reversed instantaneously with an anaesthetic. This suggests that the nociceptive input from the periphery maintains sensitisation 57.…”
Section: Where Does Tendon Pain Fit In the Continuum Model?mentioning
confidence: 99%
“…In addition, the present study will assess the effects of MWM on pressure pain threshold in CAI. The presence of localized peripheral sensitization has been previously identified in acute inversion ankle sprains [24] and in subacute ankle sprains [25]. Balance impairments in CAI are frequently reported in the literature and MWM has been found to be effective immediately after application, but there is presently insufficient research to determine the short term benefits of MWM for balance impairments [6].…”
Section: Introductionmentioning
confidence: 99%